Circulating Prolidase Activity in Patients with Myocardial Infarction - Sultan, Adnan; Zheng, Yuting; Trainor, Patrick J.; Siow, Yong; Amraotkar, Alok R.; Hill, Bradford G.; DeFilippis, Andrew P. (Frontiers in Cardiovascular Medicine, 2017)
BACKGROUND: Collagen is a major determinant of atherosclerotic plaque stability. Thus, identification of differences in enzymes that regulate collagen integrity could be useful for predicting susceptibility to atherothrombosis or for diagnosing plaque rupture. In this study, we sought to determine whether prolidase, the rate-limiting enzyme of collagen turnover, differs in human subjects with acute myocardial infarction (MI) versus those with stable coronary artery disease (CAD). METHODS: We measured serum prolidase activity in 15 patients with stable CAD and 49 patients with acute MI, of which a subset had clearly defined thrombotic MI (n=22) or non-thrombotic MI (n=12). Prolidase activity was compared across study time-points (at cardiac catheterization, T0; 6 h after presentation, T6; and at a quiescent follow-up, Tf/u) in acute MI and stable CAD subjects. We performed subgroup analyses to evaluate prolidase activity in subjects presenting with acute thrombotic versus non-thrombotic MI. RESULTS: Although prolidase activity was lower at T0 and T6 versus the quiescent phase in acute MI and stable CAD subjects (p<0.0001), it was not significantly different between acute MI and stable CAD subjects at any time point (T0, T6 and Tf/u) or between thrombotic and non-thrombotic MI groups. Preliminary data from stratified analyses of a small number of diabetic subjects (n=8) suggested lower prolidase activity in diabetic acute MI subjects compared with non-diabetic acute MI subjects (p=0.02). Conclusions: Circulating prolidase is not significantly different between patients with acute MI and stable CAD or between patients with thrombotic and non-thrombotic MI. Further studies are required to determine if diabetes significantly affects prolidase activity and how this might relate to the risk of MI.